Jual Beli Online Dalam Perspektif Hukum Islam - Risnawati, Heni; Nadhifah, Tuti; Rosita, Dian (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2024)
The aim of this research is to analyze the views of Islamic law towards online purchases and sales by considering sharia principles concerned. This research uses a qualitative approach to liberal research or literature study by searching primary sources in the form of books and journals related to this research. The results of the research show that online buying and selling according to Islamic law is permissible as long as the objects or goods being sold are not haram and do not contain elements of usury, fraud (gharar) and gambling (maisyir). The implication of this research is to provide knowledge about the behavior of trustworthy and legitimate sellers. in accordance with Islamic law.